Effects of different stabilizers on the quality of calamansi concentrate - Golez, Sharyn Gumabon (2003.)
Four lots of calamnsi concentrate samples were prepared using three different stabilizers : Gum Tragacanth (lot GT), Gellan Gum (lot GG), Xanthan Gum (lot XG) and a control lot with no added stabilizer.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Calamansi -- concentrate; Stabilizers